2017
DOI: 10.5194/nhess-2017-111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Criteria for the optimal selection of remote sensing images to map event landslides

Abstract: Abstract. We executed an experiment to determine the effects of image characteristics on event landslide mapping. In the experiment, we compared eight maps of the same landslide, the Assignano landslide, in Umbria, central Italy. Six maps were obtained through the expert visual interpretation of monoscopic and pseudo-stereoscopic (2.5D), ultra-resolution (3 × 3 cm) images taken on 14 April 2014 by a Canon EOS M photographic camera flown by an CarbonCore 950 hexacopter over the landslide, and of monoscopic and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…We report results of the three different approximations (also reported in Alvioli et al (2018)), expressed in terms of an error index E I , first introduced in Carrara (1993) and recently employed as a benchmark for selecting optimal requirements of images from remote sensing for landslide mapping (Fiorucci et al, 2018b). Results for "grid" and "SU" are obtained with a number of polygons that minimizes E I in both cases.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…We report results of the three different approximations (also reported in Alvioli et al (2018)), expressed in terms of an error index E I , first introduced in Carrara (1993) and recently employed as a benchmark for selecting optimal requirements of images from remote sensing for landslide mapping (Fiorucci et al, 2018b). Results for "grid" and "SU" are obtained with a number of polygons that minimizes E I in both cases.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In this scenario, the use of the mini-micro RPAS is practical for small areas and optimal for landslides that often cover an area that range from less than one square kilometres up to few square kilometres. Ultra-high resolution images acquired by RPAS can support the definition not only of the identification of studied landslide limit, but also the identification and mapping of main geomorphological features (Fiorucci et al, 2017). Furthermore, a sequence of RPAS acquisitions over the time can provide useful support for the study of the gravitational process evolution.…”
Section: Landslidesmentioning
confidence: 99%
“…Niethammer et al (2009) showed how RPAS could be considered a good solution for the acquisition of ultra-high resolution images with low-cost systems. Fiorucci et al (2017) compared the results of the landslide limit mapped using different techniques and found that satellite images can be considered a good solution for the identification and map of landslides over large areas. On the contrary, if the target of the study is the definition of landslide's morphological features, the use of more detailed RPAS images seemed to be the better solution.…”
Section: Landslides Recognitionmentioning
confidence: 99%
“…Also previous experiences of CNR IRPI and Civil Protection Agency in the use of small RPAS for the study of geo-hydrological processes (Giordan et al, 2015;250 Boccardo et al 2015;Fiorucci et al, 2017;Giordan et al, 2017) were useful for the definition of a correct use of these systems.…”
Section: Flood Mapping At Local Scale With High and Ultra-high Resolumentioning
confidence: 99%